Interchangeability of external player load variables from different athlete tracking systems in English Premier League soccer players - Kavanagh, R.; Mcdaid, K.; Mcdonnell, J.; Rhodes, D.; Tivey, D.; Alexander, J.; Harper, D.; Zmijewski, P.; Morgans, R. (Biology of Sport, 2026)
This study aimed to assess the interchangeability between tracking variables derived from Global Positioning System (GPS) and those of an Optical Tracking System (OTS) in elite soccer players. Twenty-six male professional outfield soccer players (age 27±4 years, height 182±6.67 cm, mass 80.73±7.74 kg) from an English Premier League (EPL) team formed the sample. Positional information was recorded using a GPS (10 Hz Apex, STATSports, Belfast, UK) and concomitantly by an OTS using six semi-automated HD cameras sampling at a frequency of 25 Hz (Second Spectrum, Los Angeles, USA). While differences exist for both total distance and high-speed running (HSR) between the GPS and OTS, the GPS was highly correlated with the OTS (r2 > 0.99). The OTS displayed the highest values across all three examined variables. Total distance was 4% higher on average when utilising the OTS, while HSR and sprint distance were 12% and 18% higher respectively. Given its importance and the differences observed, regression equations should be utilised to align GPS and OTS data to allow practitioners to evaluate running performance and optimally prepare players for the demands of the game more effectively.